2018
DOI: 10.3390/rel9120384
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Spiritual Care Competence among Expatriate Nurses Working in Saudi Arabia

Abstract: Background: In Saudi Arabia, where the majority of the nursing workforce are foreigners, little is known about perceptions of spirituality and spiritual caregiving among foreign nurses who provide nursing care to patients with varied spiritual and religious beliefs. Therefore, this study was conducted to investigate the spirituality and spiritual care competence and its predictors among expatriate Christian nurses in Saudi Arabia, who provide care for Muslim patients. Methods: A convenience sample of 302 nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
9
0
3
Order By: Relevance
“…The current study found that older nurses had lower spiritual care competence scores. This finding is supported by a Saudi Arabian study [ 25 ], which found that being in the 40–49 age range reduced spiritual care competence. The current study’s findings also showed a significant difference between nurses’ scores on spiritual care competence and those receiving spiritual care training.…”
Section: Discussionsupporting
confidence: 59%
“…The current study found that older nurses had lower spiritual care competence scores. This finding is supported by a Saudi Arabian study [ 25 ], which found that being in the 40–49 age range reduced spiritual care competence. The current study’s findings also showed a significant difference between nurses’ scores on spiritual care competence and those receiving spiritual care training.…”
Section: Discussionsupporting
confidence: 59%
“…People's life in the country is heavily influenced by their Islamic faith. Hence, the religious dimension of spiritual care is critical in the achievement of holistic care among Saudi patients (Alshehry 2018). For instance, in a study conducted by Cruz et al (2017a) among Saudi patients receiving hemodialysis treatment, the respondents reported a high degree of religiosity.…”
Section: Introductionmentioning
confidence: 99%
“…Abell et al 18 observed that participating nurses had the most positive perception on the dimension of attitude towards patients' spirituality and communication in providing spiritual care and the least positive perception on the dimension of professionalization and patient counseling in spiritual care. Alshehry 19 and Van Leeuwen and Schep‐Akkerman 10 stated that among the personal factors relating to spiritual care provision, nurses had excellent competency on the subdimensions of attitudes towards patients' spirituality and communication. Alshehry 19 reported that the highest mean scores were on attitude towards patients' spirituality (4.14 ± 0.60) and communication (4.12 ± 0.61).…”
Section: Discussionmentioning
confidence: 99%